2021
DOI: 10.1186/s12906-021-03381-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol supplementation on bone quality: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background The results from clinical trials have revealed that the effects of resveratrol supplementation on bone mineral density (BMD) and bone biomarkers are inconsistent. Our objective was to determine the effects of resveratrol supplementation on BMD and serum bone biomarkers. Methods PubMed, Cochrane library, EMBASE, Web of science and Scopus were searched up to August 24, 2020. Two reviewers independently performed the articles search and scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
(2 reference statements)
0
6
1
Order By: Relevance
“…Those outcomes provide the theoretical basis for future study on RES‐based therapies for OP sufferers. Our findings are inconsistent with the previous systematic review and meta‐analysis that suggested RES supplementation did not significantly increase BMD at lumbar spine and hip in clinical OP patients (Li, Sun, et al, 2021; Li, Yang, et al, 2021). Such discrepancies between animal and human clinical studies are not unexpectable, which provides us several implications for future research.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Those outcomes provide the theoretical basis for future study on RES‐based therapies for OP sufferers. Our findings are inconsistent with the previous systematic review and meta‐analysis that suggested RES supplementation did not significantly increase BMD at lumbar spine and hip in clinical OP patients (Li, Sun, et al, 2021; Li, Yang, et al, 2021). Such discrepancies between animal and human clinical studies are not unexpectable, which provides us several implications for future research.…”
Section: Discussioncontrasting
confidence: 99%
“…Blinding in animal models and result evaluation is often challenging for most studies. Sample size computation could prevent oversized sampling and inaccuracy caused by undersized sampling (Gupta et al, 2016) (Li, Sun, et al, 2021;Li, Yang, et al, 2021). Such discrepancies between animal and human clinical studies are not unexpectable, which provides us several implications for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthocyanins could suppress lipid accumulation in adipocytes [ 212 ] and reduce high-fat diet-induced metabolic damage [ 213 ]. Body mass index and body weight were reduced when anthocyanin supplementation was 300 mg/d or less for 4 weeks [ 214 ]. Cyanidin 3-caffeoyl-p-hydroxybenzoylsophoroside-5-glucoside as an anthocyanin isolated from purple-fleshed sweet potato showed hypoglycemic effects by specifically suppressing hepatic glucose output [ 215 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 24-month RES (RESHAW) trial of healthy ageing in women showed that regular 75 mg resveratrol supplementation twice daily had the potential to slow bone loss in the lumbar spine and femoral neck, which is common at fracture sites in postmenopausal women without significant osteoporosis ( Wong et al, 2020 ). However, a systematic review and meta-analysis showed that RES supplements did not show any significant effect on BMD or serum bone markers ( Li Q. et al, 2021 ). Therefore, further research utilizing better organized multicenter randomized trials is necessary so that physicians can provide more advice for clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%